PENGARUH ROTASI AUDITOR, PROFITABILITAS, LEVERAGE, UMUR PERUSAHAAN TERHADAP ASIMETRI INFORMASI DAN PERAN HUBUNGAN POLITIK DI PERBANKAN INDONESIA - Pina, Pina; Tanujaya, Kennardi (Jurnal Aplikasi Akuntansi, 2024)
This research aims to determine the effect of audit rotation, profitability, Leverage and company age on information asymmetry with political relations as a moderating variable in banking in Indonesia. The data studied is 32 banks registered on the IDX from 2016 to 2022. This research found that auditor rotation did not influence information asymmetry. Even though political relations were added as moderation, auditor rotation did not affect information asymmetry. Profitability and Leverage have a negative influence on information asymmetry, and company age has a positive impact on information asymmetry. The results of this research imply that investors need to consider company characteristics in detecting information asymmetry in financial reports.